2015
DOI: 10.1016/j.jeurceramsoc.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale assessment of the crystallization onset in silicon carbonitride

Abstract: Within the present study, atomic-scale electron microscopy investigation on the crystallization behavior of polysilylcarbodiimide-derived SiCN was performed. The as-prepared SiCN sample was found to be homogeneous and consisted of amorphous silicon nitride nano-domains dispersed within an amorphous, highly entangled graphene-like carbon matrix. Annealing of the sample at 1400 • C induced a slight increase of the ordering of the carbon phase. Additionally, the crystallization onset of the silicon nitride has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…4 These distinct advantages of SiBCN ceramics over traditional PDCs have inspired the development of SiBCN ceramics with much improved strengths and thermal stability with respect to oxidation and crystallization. 4 These distinct advantages of SiBCN ceramics over traditional PDCs have inspired the development of SiBCN ceramics with much improved strengths and thermal stability with respect to oxidation and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…4 These distinct advantages of SiBCN ceramics over traditional PDCs have inspired the development of SiBCN ceramics with much improved strengths and thermal stability with respect to oxidation and crystallization. 4 These distinct advantages of SiBCN ceramics over traditional PDCs have inspired the development of SiBCN ceramics with much improved strengths and thermal stability with respect to oxidation and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…5 nm and thus larger than that of the clusters identified in [31]. This might rely on two aspects: (i) different crystallization behavior of the coatings as compared to bulk powder materials (though here the opposite trend would be expected, i.e., size of Si 3 N 4 precipitation in coatings should be smaller than that observed in bulk powders, as reported in [33] -the reason might be the extent of the free surface, much large in powders than in monolithic samples, which was shown promote the crystallization of Si 3 N 4 [33]); or (ii) the content of segregated carbon.…”
Section: Crystalline Phase Composition and Microstructure Of The Sicnmentioning
confidence: 79%
“…The formation of ␣-silicon nitride has been attributed to the diffusion of silicon atoms via dangling bonds in the amorphous silicon nitride network, which was observed by a recent atomic resolution STEM study on PV bulk ceramics [31], showing that the onset of crystallization of ␣-silicon nitride (clusters with average sizes of 0.8, 1.5 and 2.1 nm) occurs at 1400 • C.…”
Section: Crystalline Phase Composition and Microstructure Of The Sicnmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been shown that especially amorphous quaternary a‐SiBCN and ternary a‐SiCN can fulfill these demands . Both, the bulk (polymer to ceramic transformation from a single polymeric polyborosilazane) and the SiBCN thin films (DC magnetron sputtering from segmented B 4 C target with p ‐type Si stripes) were reported to possess an exceptional thermal stability even above 1500°C that was reported as an ultimate temperature for Si 3 N 4.…”
Section: Introductionmentioning
confidence: 99%